Calcitriol modulates the CD46 pathway in T cells. - Karoline Kickler; Siobhan Ni Choileain; Anna Williams; Anna Richards; Anne L Astier (PLoS ONE)
The complement regulator CD46 is a costimulatory molecule for human T cells that induces a regulatory Tr1 phenotype, characterized by large amounts of IL-10 secretion. Secretion of IL-10 upon CD46 costimulation is largely impaired in T cells from patients with multiple sclerosis (MS). Vitamin D can exert a direct effect on T cells, and may be beneficial in several pathologies, including MS. In this pilot study, we examined whether active vitamin D (1,25(OH)(2)D(3) or calcitriol) could modulate the CD46 pathway and restore IL-10 production by CD46-costimulated CD4+ T cells from patients with MS. In healthy T cells, calcitriol profoundly affects the phenotype of CD46-costimulated CD4+ T cells, by increasing the expression of CD28, CD25, CTLA-4 and Foxp3 while it concomitantly decreased CD46 expression. Similar trends were observed in MS CD4+ T cells except for CD25 for which a striking opposite effect was observed: while CD25 was normally induced on MS T cells by CD46 costimulation, addition of calcitriol consistently inhibited its induction. Despite the aberrant effect on CD25 expression, calcitriol increased the IL-10:IFNγ ratio, characteristic of the CD46-induced Tr1 phenotype, in both T cells from healthy donors and patients with MS. Hence, we show that calcitriol affects the CD46 pathway, and that it promotes anti-inflammatory responses mediated by CD46. Moreover, it might be beneficial for T cell responses in MS.